Local control and short-term outcomes after VATS segmentectomy vs lobectomy for pT1c pN0 NSCLC (2–3 cm). (1st June 2022) - Forster, C; Abdelnour-Berchtold, E; Bédat, B; Perentes, J Y; Sauvain, M-O; Christodoulou, M; Triponez, F; Karenovics, W; Krueger, T; Gonzalez, M
Abstract: Objective: Pulmonary segmentectomy has shown comparable oncological results to lobectomy for non-small cell lung cancers (NSCLC) of less than 2 cm. However, controversy remains for tumors of larger size. The aim of this study was to compare short-term outcomes and local control in pT1c pN0 NSCLC that were intentionally treated by VATS segmentectomy or lobectomy. Methods: Multicenter retrospective study from January 2014 to October 2021 of 162 consecutive patients undergoing complete (R0) anatomical resections for pT1c pN0 NSCLC. Two groups, VATS lobectomy (VL) or VATS segmentectomy (VS) were defined according to the extension of the resection. Patients' characteristics, postoperative outcomes and survival were compared. Results: In total, 162 patients underwent VL (n=81) or VS (n=81). Except for age (median of 68 vs 71 years, p=0.034) and past medical history of cancer (32% vs 48%, p=0.038), there was no difference between VL and VS in terms of demographics and comorbidities (table1). Segmentectomies were performed in upper lobes in 68% and single segments represented 46% of all cases. Conversion thoracotomy rate was 5% in both groups. Morbidity were similar in both groups (34% vs 30%, p=0.5). The median time for chest tube removal (3 vs 2 days, p=0.002) and median LOS (6 vs 5 days, p=0.039) were in favor of the VS group. Significantly larger tumor (25 mm vs 23.5 mm p=0.001) and an increased number of lymph nodes removal (median 14 vs 10, p<0.001) were found in the VL group. During the follow-up (median: 31 months), no statistical difference was found for local and distant recurrence in VL groups (12.3%) and VS group (6.2%) (p=0.414). Overall survival was comparable in-between both groups (p=0.166). Conclusion: Despite a short follow-up, our preliminary data shows that local control is comparable for VATS lobectomy and VATS segmentectomy. Further prospective randomized trials are needed to corroborate these results.